Zaczarowany świat. (Gdynia : [s.n.], 1947)
Afisz. inf. o projekcji filmu w kwietniu 1947 r.
Keywords: Kina -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Kino sowieckie -- 1929-1945 -- druki ulotne